The Art of Occupation Crime and Governance in American-Controlled Germany, 1944-1949. - Kehoe, Thomas J. 1980- (War and Society in North America Ser., 2019)
This important contribution to American and German social, military, and police histories, as well as historical criminology offers the first comprehensive exploration of criminality, policing, and both German and American fears around the realities of conquest and potential resistance amid the looming threat from communism in an emergent Cold War.